Management Practices in Hospital Administration: a study of the Challenges Faced by the Healthcare Organisation in South India - Varghese, Bindi (Atna Journal of Tourism Studies, 2021)
This paper accentuates the need for quality assurance and standardization norms for hospital administration which is the need of the hour. Lack of effective administration practices in the hospital and hospitality sector necessitate the need for a total quality management approach in the Healthcare Sector. Application of quality control systems is a vital aspect that hospitals in South India cannot disregard. It would lead the South in a new direction by ensuring quality and enhancing customer satisfaction. Hence, this paper makes an attempt to understand the hospital management practices in South India effectively. The research addresses Medical Tourism as a ‘cost effective’ private medical care initiative in collaboration with the tourism industry for patients needing surgical and other forms of specialised treatment. This process is being facilitated by the corporate sector involved in medical care as well as the tourism industry – both private and public. There is also a constant effort taken by corporate hospitals to support medical tourism to its fullest potential. India today has copious opportunities to compete with other developed nations and building a quality health care system of its own.